A framework for the evaluation of hotel property development projects - Popovic, Gabrijela; Stanujkic, Dragisa; Karabasevic, Darjan (International Journal of Strategic Property Management, 2019)
The main goal of the manuscript is to propose the framework that would facilitate the selection of hotel construction projects for an investment based on the application of the WS PLP method. The key reason why the WS PLP method is used is reflected in its ability to more accurately express decision-makers’ stand regarding the desired preference ratings of criteria by incorporating ppr values into the decision-making process. Also, the WS PLP method implies the introduction of the compensation coefficient, which provides a possibility of the decision-maker’s selection between an alternative that has the best matching with the preferred performance ratings expressed through ppr values and the one that has the best overall performance ratings. The applicability and effectiveness of the proposed framework are demonstrated through a real case study on the five types of the hotels that should be constructed on Kopaonik Mountain in Serbia.